Guanabenz Reverses a Key Behavioral Change Caused by Latent Toxoplasmosis in Mice by Reducing Neuroinflammation - Jennifer Martynowicz (American Society for Microbiology, 2019)
ABSTRACT Toxoplasma gondii is an intracellular parasite that has infected one-third of humans. The infection is permanent because the replicative form (tachyzoite) converts into a latent tissue cyst form (bradyzoite) that evades host immunity and is impervious to current drugs. The continued presence of these parasitic cysts hinders treatment and leads to chronic infection that has been linked to behavioral changes in rodents and neurological disease in humans. How these behavioral changes occur, and whether they are due to parasite manipulation or the host response to infection, remains an outstanding question. We previously showed that guanabenz possesses antiparasitic activity; here, we show that guanabenz reproducibly lowers brain cyst burden up to 80% in chronically infected male and female BALB/cJ mice when given intraperitoneally but not when administered by gavage or in food. Regardless of the administration route, guanabenz reverses Toxoplasma-induced hyperactivity in latently infected mice. In contrast, guanabenz increases cyst burden when given to chronically infected C57BL/6J mice yet still reverses Toxoplasma-induced hyperactivity. Examination of the brains from chronically infected BALB/cJ and C57BL/6J mice shows that guanabenz decreases inflammation and perivascular cuffing in each strain. Our study establishes a robust model for cyst reduction in BALB/cJ mice and shows for the first time that it is possible to reverse a key behavioral change associated with latent toxoplasmosis. The rescue from parasite-induced hyperactivity correlates with a decrease in neuroinflammation rather than reduced cyst counts, suggesting that some behavioral changes arise from host responses to infection. IMPORTANCE Toxoplasma gondii is a common parasite of animals, including up to one-third of humans. The single-celled parasite persists within hosts for the duration of their life as tissue cysts, giving rise to chronic infection. Latent toxoplasmosis is correlated with neurological dysfunction in humans and results in dramatic behavioral changes in rodents. When infected, mice and rats adapt behaviors that make them more likely to be devoured by cats, the only host that supports the sexual stage of the parasite. In this study, we establish a new mouse model of tissue cyst depletion using a drug called guanabenz and show that it is possible to reverse a key behavior change back to normal in infected animals. We also show that the mechanism appears to have nothing to do with parasite cyst burden but rather the degree of neuroinflammation produced by chronic infection.